Pressure evolution of the electronic structure of non-centrosymmetric EuRhGe3. (15th July 2021) - Utsumi, Y; Batistić, I; Balédent, V; Shieh, S R; Dhami, N S; Bednarchuk, O; Kaczorowski, D; Ablett, J M; Rueff, J P
Abstract: Among europium compounds, pressure induced valence transitions and/or intermediate valence states are often observed. In such systems, applying pressure of several GPa can drive a Eu valence from divalent to almost trivalent. Non-centrosymmetric EuRhGe3 possesses magnetic Eu 2+ ions and exhibits antiferromagnetic ordering at ∼11 K at ambient pressure. Pressure resistant magnetic ordering and stable divalent Eu state have been reported in EuRhGe3 . Here, we study the pressure evolution of the Eu valence of EuRhGe3 by high resolution x-ray absorption spectroscopy using the partial fluorescence yield method. Our study reveals a successive increase of the Eu valence with increasing pressure without any valence transition. The obtained mean Eu valence approaches ∼2.4 around 40 GPa at 300 K. The experimental data are also analyzed by a full multiplet configuration interaction calculation based on the single impurity Anderson model. The analysis reveals a decrease of the Eu 4 f orbital occupation by applying pressure. Pressure evolution of the electronic structure studied by density functional theory suggests that the Rh ions have little contribution to the pressure evolution of the Eu valence, while it implies an active involvement of the Ge ions.